2022
DOI: 10.1002/cbin.11969
|View full text |Cite
|
Sign up to set email alerts
|

RAB5C, a new mRNA binding target of HuR, regulates breast cancer cell proliferation

Abstract: The posttranscriptional control of gene expression mediated by RNA‐binding proteins (RBPs) is essential to determine tumor cell fate. HuR is an RBP with increased expression in various cancer types. This study aimed to clarify the regulatory mechanism of HuR's contribution to breast cancer (BC) cell proliferation by inducing RAB5C expression. First, we analyzed the expression level of HuR and RAB5C in BC tissues and cell lines by immunohistochemistry, qRT‐PCR, and western blot. Next, to further investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…RAC1 and CDC42 acted together as downstream signals of RAS gene in the MAPK pathway to regulate cytoskeletal movement [33]. This may be a possible reason for the enhanced proliferation of HER2 L796P [34]. In phosphorylated proteomics studies, we found more differentially expressed protein sites related to MAPK and PI3K/AKT/TOR pathways.…”
Section: Discussionmentioning
confidence: 97%
“…RAC1 and CDC42 acted together as downstream signals of RAS gene in the MAPK pathway to regulate cytoskeletal movement [33]. This may be a possible reason for the enhanced proliferation of HER2 L796P [34]. In phosphorylated proteomics studies, we found more differentially expressed protein sites related to MAPK and PI3K/AKT/TOR pathways.…”
Section: Discussionmentioning
confidence: 97%
“…It primarily involves vesicle docking and fusion processes, ensuring vesicles bind to their correct receptors. Wang et al discovered that RAB5C is a new mRNA binding target of HuR, regulating breast cancer cell proliferation [40] . Zhang et al found that RAB5C is a tumor suppressor in thyroid cancer [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that HuR regulates mRNA expression either by stabilizing messages or by influencing their translation [ 30 , 31 , 32 ]. For instance, HuR bound to the 3′UTR of RAB5C, increasing RAB5C mRNA stability [ 33 ]. HuR affects FGFRL1 expression by binding to and stabilizing FGFRL1 mRNA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%